(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Chronic obstructive pulmonary disease is one of the most common diseases of the respiratory system in the modern world. According to the World Health Organization, COPD ranks third among the causes of death worldwide. In Russia, more than 11 million people suffer from this disease, and many of them do not even suspect its presence at the early stages.